High side MOSFET driver design using discrete components for low voltage applications - Pungut, Ibrahim; Rosnazri, Ali; Ismail, Daut, Prof. Dr.; Soib, Taib, Prof. Madya Dr.; Dina Maizana, Maiz Ahmad; Risnidar Chan Bahaudin, Ir. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.